2011
DOI: 10.1071/rdv23n1ab97
|View full text |Cite
|
Sign up to set email alerts
|

97 Improved Cryopreservation of Domestic Cat Spermatozoa in a Soy Lecithin-Based Extender

Abstract: Development of a chemically defined, plant-based cryopreservation media would reduce extender variability and the potential for transmission of zoonotic pathogens compared with traditional egg-yolk-based extenders. The objective of this study was to compare effects of egg yolk- and soy lecithin-based cryopreservation media and the temperature of glycerol addition on sperm parameters following freezing and thawing of domestic cat spermatozoa. Fresh semen was collected by manual stimulation on 3 separate occasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The current study revealed that 0.5% of SL can replace the egg yolk in the Tris dilution, so that the sheep sperm can be stored at 0°C for a longer time. It can be concluded from the literature that the optimal concentration range of SL for cryopreservation is 0.8% in dogs [ 20 ] to 1% in rams [ 14 ], humans [ 21 ] and cats [ 22 ] and goats [ 23 ]. The reason for this difference in addition of SL is that the differences in species are related to the differences of sperm plasma membrane composition between species [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study revealed that 0.5% of SL can replace the egg yolk in the Tris dilution, so that the sheep sperm can be stored at 0°C for a longer time. It can be concluded from the literature that the optimal concentration range of SL for cryopreservation is 0.8% in dogs [ 20 ] to 1% in rams [ 14 ], humans [ 21 ] and cats [ 22 ] and goats [ 23 ]. The reason for this difference in addition of SL is that the differences in species are related to the differences of sperm plasma membrane composition between species [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soy lecithin, mainly composed of phosphatidylcholine [6], emerged as an alternative to components of animal origin. Many studies have confirmed the suitability of soy lecithin on sperm, including goat [7][8][9][10], ram [11][12][13], human [14] and cat [15], and several commercial formulations are currently available (e.g., Andromed, BIOXCell).…”
Section: Introductionmentioning
confidence: 99%
“…Lecithin is a valuable plant origin to prevent sperm cold shock, because it consists of glycerol, two fatty acids, phosphate group and choline which play an important role in protecting sperm cell membrane. The previous facts has been developed and utilized to preserve spermatozoa of human (Jeyendran et al, 2008), domestic cat (Vick et al, 2010), stallion (Papa et al, 2011), ram (Khalifa and Abdel-Hafez, 2014), buffalo (Akhter et al, 2012), goat (Chelucci et al, 2015) and bovine bull (El-Sisy et al, 2016).…”
Section: Introductionmentioning
confidence: 99%